The organization of cloud-scale gas density structure: high-resolution CO versus 3.6 μm brightness contrasts in nearby galaxies - Meidt, Sharon E.; Leroy, Adam K.; Querejeta, Miguel; Schinnerer, Eva; Sun, Jiayi; Wel, Arjen van der; Emsellem, Eric; Henshaw, Jonathan; Hughes, Annie; Kruijssen, Diederik; Rosolowsky, Erik; Schruba, Andreas; et al. (The astrophysical journal, 2021)
In this paper we examine the factors that shape the distribution of molecular gas surface densities on the 150 pc scale across 67 morphologically diverse star-forming galaxies in the PHANGS-ALMA CO (2-1) survey. Dividing each galaxy into radial bins, we measure molecular gas surface density contrasts, defined here as the ratio between a fixed high percentile of the CO distribution and a fixed reference level in each bin. This reference level captures the level of the faint CO floor that extends between bright filamentary features, while the intensity level of the higher percentile probes the structures visually associated with bright, dense interstellar medium features like spiral arms, bars, and filaments. We compare these contrasts to matched percentile-based measurements of the 3.6 μm emission measured using Spitzer/IRAC imaging, which trace the underlying stellar mass density. We find that the logarithms of CO contrasts on 150 pc scales are 3-4 times larger than, and positively correlated with, the logarithms of 3.6 μm contrasts probing smooth nonaxisymmetric stellar bar and spiral structures. The correlation appears steeper than linear, consistent with the compression of gas as it flows supersonically in response to large-scale stellar structures, even in the presence of weak or flocculent spiral arms. Stellar dynamical features appear to play an important role in setting the cloud-scale gas density in our galaxies, with gas self-gravity perhaps playing a weaker role in setting the 150 pc scale distribution of gas densities.
Gesehen am 18.02.2022